Aplicação de modelo para fluxo de água no solo visando a automação de sistema de irrigação - Cruz, Tadeu Macryne Lima (2015)
The Knowledge of the water flow into the soil is very important to establish an appropriate water management. This thesis was divided into three chapters whose general objective is to apply a water flow model on the ground in real time by the finite element method to simulate and determine the required irrigation time. Considering the importance of physical soil moisture monitoring was developed a multiplexed data acquisition system analysis tool as the water content in the soil profile. For monitoring soil moisture (θ) were installed 15 capacitance sensors arranged in grid form in the soil profile. The multiplexer board allowed us to evaluate the formation of the wet bulb and estimate the dimensions of wet soil with drip irrigation. With the evaluation of the wet bulb and data of the properties and soil physical parameters were applied a model a computer model that uses the technique of finite elements to provide vertical water flow in unsaturated soil. In soil parameter sought to approximate the initial conditions of simulation control and soil moisture values on which the model would process the results in order to compose the same situation encountered in the field. The multiplexer board developed was efficient to make acquisitions of soil moisture data, using capacitance sensors FDR, with versatility and robustness against bad weather and allowed us to evaluate the formation of the wet bulb in the soil. The maps of the ground water flow, after calibration of the model, simulations have provided satisfactory transient dynamics of the water in the soil, allowing its use in determining the irrigation time.